The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fimmu.2022.949787
|View full text |Cite
|
Sign up to set email alerts
|

Saliva antibody-fingerprint of reactivated latent viruses after mild/asymptomatic COVID-19 is unique in patients with myalgic-encephalomyelitis/chronic fatigue syndrome

Abstract: BackgroundMyalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a chronic disease considered to be triggered by viral infections in a majority of cases. Symptoms overlap largely with those of post-acute sequelae of COVID-19/long-COVID implying common pathogenetic mechanisms. SARS-CoV-2 infection is risk factor for sustained latent virus reactivation that may account for the symptoms of post-viral fatigue syndromes. The aim of this study was first to investigate whether patients with ME/CFS and healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 58 publications
(75 reference statements)
5
21
1
Order By: Relevance
“…Autoimmune reactions in adult patients and allergic reactions in children appear to be critical factors (Ortona & Malorni, 2022; Osmanov et al ., 2022). Reactivated latent viruses (which may affect long COVID symptoms) may also appear after mild asymptomatic COVID-19 (Apostolou et al ., 2022). Historically, immune genes protective against the bubonic plague, especially in Northern European populations, are associated with increased susceptibility to autoimmune diseases (Klunk et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Autoimmune reactions in adult patients and allergic reactions in children appear to be critical factors (Ortona & Malorni, 2022; Osmanov et al ., 2022). Reactivated latent viruses (which may affect long COVID symptoms) may also appear after mild asymptomatic COVID-19 (Apostolou et al ., 2022). Historically, immune genes protective against the bubonic plague, especially in Northern European populations, are associated with increased susceptibility to autoimmune diseases (Klunk et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…At 3-6 months after infection, virus-specific antibodies in saliva were substantially induced, indicating a strong reactivation of all three viruses in both cohorts. In patients with ME/CFS, however, antibody responses were significantly stronger, in particular against EBV-encoded nuclear antigen-1 (EBNA1) than in the controls ( 101 ).…”
Section: Biological Mechanisms Of Lcmentioning
confidence: 99%
“…Although this reflects a reasonable explanation, the presence of persistent latent or asymptomatic virus infection and the rise of antibodies should be proven more robustly. 77 Other than the above, Finlay et al 78 reported that infiltration of T cells expressing interferon-γ to the olfactory epithelium could be the cause of long-term smell loss after COVID-19 infection. They examined 24 olfactory epithelial biopsy specimens in PASC patients and found T cell-mediated inflammatory signaling was accompanied by a reduced number of olfactory sensory neurons.…”
Section: Activated Autoimmune Systemmentioning
confidence: 99%